Identifying level of awareness on sufficiency of safety and health requirements amongst contractors / Nor Suzila Lop, Izatul Farrita Mohd Kamar and Norazlin Mat Salleh - Lop, Nor Suzila; Mohd Kamar, Izatul Farrita; Mat Salleh, Norazlin (2012)
Construction site is dangerous by its nature and are prone to accidents. Extensive efforts have previously been taken in order to minimise its risk. By providing adequate budget for safety requirements during tendering, it will help to concern more about the safety. This research proposes to look into the level of awareness among construction players regarding the adequacy of safety and health requirements on site during construction stage that lead to non-compliance of safety and health regulations. Objective of this research is to identify the level of awareness among construction layers and to recommend the awareness improvement towards safety and health requirements on construction site. The data for this research will be collected via questionnaires which were distributed to the Class A contractors registered with PKK in Perak. Descriptive statistic will be used to analyse the data. The results will indicate the level of awareness of the different parties in order to resolve the problem of the inadequacy of the construction site safety and health requirements.